Association of the Microbiota and Pancreatic Cancer: Opportunities and Limitations - Chen, Zhou; Zhang, Shaofeng; Dong, Shi; Xu, Hao; Zhou, Wence (Frontiers in Immunology, 2022)
The human body is thoroughly colonized by a wide variety of microorganisms, termed microbiota. Pancreatic cancer, one of the most aggressive forms of cancer, is no exception. The microbiota of pancreatic cancer largely influences and even dominates the occurrence, development and outcome of pancreatic cancer in many ways. Studies have shown that microbiota could change the malignant phenotype and prognosis of pancreatic cancer by stimulating persistent inflammation, regulating the antitumor immune system, changing the tumor microenvironment and affecting cellular metabolism. This is why the association of the microbiota with pancreatic cancer is an emerging area of research that warrants further exploration. Herein, we investigated the potential microbial markers of pancreatic cancer, related research models, the mechanism of action of microbiota in pancreatic cancer, and pancreatic cancer-microbiota-related treatment.